Thomas G. Corcoran papers - Corcoran, Thomas G.
Correspondence, memoranda, speeches, writings, notes, reports, briefs, opinions, testimonies, family papers, business records, newspaper clippings, printed material, and other papers chiefly documenting Corcoran's private legal practice and his government service during the first two presidential terms of Franklin D. Roosevelt. Includes material pertaining to his service in the New Deal era as legislative draftsman, litigator, employment bureau director, and speech writer.
Subjects include politics, political reform, campaigns, domestic issues, foreign affairs, China, reorganization of the Supreme Court in 1937, Securities and Exchange Commission, taxation, the 14th Air Force Association and the Flying Tigers, and minerals and mining. Individuals, institutions, and organizations represented include Anna Chennault, Claire Lee Chennault, Benjamin V. Cohen, John Bowden Connally, Walter F. George, Oliver Wendell Holmes, Lyndon B. Johnson, George W. Norris, John J. O'Connor, Jr., the American Law Institute, Brown University, District of Columbia Bar, and Harvard University.
Documents his work with Cotton, Franklin, Wright & Gordon, New York, N.Y., (1927-1932) and with Corcoran, Youngman & Rowe (1941-1981). Includes material on clients such as China Defense Supplies, American International Underwriters, Mme. Paul DuPuy, Ernest K. Halbach, Sterling Drug, Tennessee Gas Transmission Company, and United Fruit Company.
Correspondents include Bernard M. Baruch, Francis Biddle, Hugo Lafayette Black, Edward B. Burling, Anna Chennault, Benjamin V. Cohen, John Bowden Connally, William Denman, William O. Douglas, Edward C. Eicher, James Aloysisus Farley, Jerome Frank, Felix Frankfurter, Harry Lloyd Hopkins, Hubert H. Humphrey, Harold L. Ickes, Joseph P. Kennedy, Robert Houghwout Jackson, Lyndon B. Johnson, James McCauley Landis, Frank Murphy, Claude Pepper, Sam Rayburn, Franklin D. Roosevelt, Samuel Irving Rosenman, James H. Rowe, Walter Bedell Smith, and Stuart Symington.
Library of Congress Geography and Map Division.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
Library of Congress African and Middle Eastern Division.
Library of Congress Rare Book and Special Collections Division.
Lawyer. Full name: Thomas Gardiner Corcoran. Born 1900; died 1981.
Keywords: Baruch, Bernard M. -- 1870-1965 -- Correspondence; Biddle, Francis, -- 1886-1968 -- Correspondence; Black, Hugo LaFayette, -- 1886-1971 -- Correspondence; Burling, Edward B. -- 1870-1966 -- Correspondence; Chennault, Anna; Chennault, Anna -- Correspondence; Chennault, Claire Lee, -- 1893-1958.; Cohen, Benjamin V; Cohen, Benjamin V. -- Correspondence; Connally, John Bowden, -- 1917-1993.; Connally, John Bowden, -- 1917-1993 -- Correspondence; Denman, William, -- 1872-1959 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Dupuy, Paul, -- Mme; Eicher, Edward C. -- Correspondence; Farley, James A. -- 1888-1976 -- Correspondence; Frank, Jerome, -- 1889-1957 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; George, Walter F. -- 1878-1957.; Halbach, Ernest K; Holmes, Oliver Wendell, -- 1841-1935.; Hopkins, Harry L. -- 1890-1946 -- Correspondence; Humphrey, Hubert H. -- 1911-1978 -- Correspondence; Ickes, Harold L. -- 1874-1952 -- Correspondence; Kennedy, Joseph P. -- 1888-1969 -- Correspondence; Jackson, Robert Houghwout, -- 1892-1954 -- Correspondence; Johnson, Lyndon B. -- 1908-1973.; Johnson, Lyndon B. -- 1908-1973 -- Correspondence; Landis, James McCauley, -- 1899-1964 -- Correspondence; Murphy, Frank, -- 1890-1949 -- Correspondence; Norris, George W. -- 1861-1944.; O'Connor, John J., -- Jr; Pepper, Claude, -- 1900-1989 -- Correspondence; Rayburn, Sam, -- 1882-1961 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Rosenman, Samuel I. -- 1896-1973 -- Correspondence; Rowe, James H. -- 1909-1984 -- Correspondence; Smith, Walter Bedell, -- 1895-1961 -- Correspondence; Symington, Stuart, -- 1901-1988 -- Correspondence; Corcoran family; United States. -- Securities and Exchange Commission; United States. -- Supreme Court -- History; 14th Air Force Association (U.S.); 14th Air Force Association (U.S.). -- Flying Tigers; American International Underwriters; American Law Institute; Brown University; China Defense Supplies; Corcoran, Youngman and Rowe; Cotton, Franklin, Wright and Gordon; District of Columbia Bar; Harvard University; Sterling Drug; Tennessee Gas Transmission Company; United Fruit Company; Mines and mineral resources; New Deal, 1933-1939.; Political campaigns; Practice of law